A Brief Overview of the Degradation of Cyanides and Phenols in the Environment With Reference to the Coke Oven Industry Discharge. Issue 7 (1st July 2022) - Maharana, Jayashree; Pandey, Sony; Dhal, Nabin Kumar
Abstract: The main elements of mother earth, like air, water, and soil, are constantly being poisoned due to inadequate waste treatment and the lack of such technologies. Few chemicals such as cyanides and phenols are not environmentally benign, yet they can be spontaneously removed in nature unless their amount is overwhelming. Therefore, these compounds must be treated in the waste/wastewater at the point of discharge. However, many of the physical and chemical waste treatment technologies are expensive, require high maintenance, and are unsustainable because of the formation of other life-threatening chemical by-products. When released into the environment, cyanide and phenol often enter into the ecosystem and disturb all trophic levels. When these chemicals are allowed to degrade themselves in nature, the ecosystem breaks them down into nontoxic organic constituents. Many microbes like bacteria, algae, and fungi have been reported to detoxify these pollutants with their enzymatic action without any toxic by-products. This review highlights the fact that only a few genera and species of microorganisms have been exploited for this purpose. So far very few studies have been carried out on defining the role of uncultured microorganisms in the cyanide and phenol cycles in nature. Graphical Abstract: UF0001